A Reflection on Terrorism and Inequalities - Federici, Maria Caterina (Italian Sociological Review, 2017)
The article considers the theme of terrorism, with regard to the social representation of the ‘other than selves’ in Europe. Foreign fighters and autochthonous jihadists are young radicalized people, often born in Europe. This fact generates processes of stigmatization for migrants and peculiar social groups. The paper discusses, in a sociological perspective with historical references, the presence of non-national social groups in Southern Europe. Mediterranean sea historically was the bridge and the locus for encounters. At the same time it was a place of conflicts and wars. However, the presence of the ‘strangers’ in Europe has for centuries been the root of European cultural diversity.